STUDI PRAKTIK BAGI HASIL ANTARA PEMILIK DAN PEMELIHARA SAPI DI KELURAHAN SENDANG MULYA SARI KECAMATAN TONGAUNA KABUPATEN KONAWE - Ahmad Ikhsan; Baheri Baheri; Nuddin Nuddin (JEP (Jurnal Ekonomi Pembangunan), 2018)
This research aims to find out how the implementation system for the results and how the view of Islamic economy against the practice for the results the maintenance of cattle in Sendang Mulya Sari Urban Village, Tongauna, Sub-District, Konawe Regency. The population in this research is the owner and maintainer of the cow running contract for results the maintenance of beef with a total of 19 people. Analysis tools used are descriptive analysis by processing primary data obtained by interview and questionnaire. Based on research it can be concluded that the practice for the results which was carried out by people in the Sendang Mulya Sari Urban Village, using the method of profit the revenue sharing, the mudharabah types included in the muthlaqah. While economic review of Syariah for the results meet the tenets of mudharabah but have qualified legitimately mudharabah contract for the results mainly on the calf in turn